The Impact of Aquatic Activity Program on Physical Fitness and Body Composition in Adolescents with Intellectual Disabilities: A Randomized Controlled Trial - Nalbant, Ozgur; Nalbant, Sibel; Yilmaz, Atike; Ercavus, Berre Cagla; Uzum, Selcuk Turhan; Ozdogan, Ferhat; Oguz, Busra (Sagamore Publishing Llc, 2025)
Adolescents with intellectual disabilities (ID) often struggle with maintaining healthy body composition and physical fitness. This randomized controlled trial (RCT) aimed to assess the effects of an 8-week aquatic activity (AA) program on body composition and physical fitness in adolescents with mild ID. A total of 19 adolescents with mild ID (16.10 +/- 0.7 years in the aquatic activity group [AAG], 15.55 +/- 1.1 years in the control group [CG]) were randomly assigned to either the AAG (n = 10) or CG (n = 9). The AAG participated in aquatic activity three times a week for 60 minutes, incorporating resistance exercises in addition to the natural resistence created by physical activity in water. The CG maintained their usual routine. Body composition (weight, BMI, body fat percentage) and physical fitness were assessed before and after the intervention. The AAG showed significant improvements in physical fitness, body weight, and BMI compared to the CG (p < 0.05). However, no significant changes were observed in body fat percentage. These results suggest that aquatic activity may be beneficial for improving body composition and physical fitness in adolescents with ID. Aquatic activity can enhance body composition and physical fitness in adolescents with ID. Future research should explore the combined effects of exercise and diet on physical fitness and body composition in this population.
Keywords: Fitness; Body Composition; Rct Intervention; Aquatic; Activities; Rehabilitation; Exercise Program; Health Out-Comes